(untitled) (Journal of EAHIL, 2023)
Medical librarians know very well that they must build new competencies to offer relevant services and develop new library services. In a workshop at the EAHIL conference 2023, suggestions for competency building, and how libraries can build competency, were discussed. Positive and enthusiastic participants came up with many ideas: different types of clubs, webinars and courses, knowledge sharing with colleagues, regularly block out time, or just solve your tasks in a new way. The experiences showed that competency building in a busy work schedule is possible. The initiatives have in common that they portray an attitude to learn more, but also the willingness to organise activities and share competency with colleagues.